2021
DOI: 10.1097/jsm.0000000000000998
|View full text |Cite
|
Sign up to set email alerts
|

Do High-Volume Injections Affect the Ultrasonographic Neovascularization in Chronic Achilles Tendinopathy? A Randomized Placebo-Controlled Clinical Trial

Abstract: Objective:High-volume injections (HVIs) are thought to target neovascularization in chronic midportion Achilles tendinopathy (AT), yet the mechanism has not been clarified. Therefore, we aim to evaluate whether a HVI decreases ultrasonographic Doppler flow in patients with chronic midportion AT.Design:A double-blind, randomized, placebo-controlled clinical trial.Setting:Sports medicine department at a district general hospital.Patients:Sixty-two patients with clinically diagnosed chronic midportion AT were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…High-volume injections have been used to treat midsubstance Achilles tendinopathy, with the theorized mechanism of action consisting of the disruption of neovascularization. In a double-blinded RCT, van Oosten et al found no reduction in Doppler blood flow in 62 subjects with chronic midsubstance Achilles tendinopathy following a high-volume injection (50 mL) compared with a placebo (2-mL injection) 16 . The amount of post-injection hypervascularity did not correlate with clinical outcomes, suggesting that the disruption of neovessels may not be a mechanism of action of high-volume injection used to treat midsubstance Achilles tendinopathy.…”
Section: Foot and Anklementioning
confidence: 99%
“…High-volume injections have been used to treat midsubstance Achilles tendinopathy, with the theorized mechanism of action consisting of the disruption of neovascularization. In a double-blinded RCT, van Oosten et al found no reduction in Doppler blood flow in 62 subjects with chronic midsubstance Achilles tendinopathy following a high-volume injection (50 mL) compared with a placebo (2-mL injection) 16 . The amount of post-injection hypervascularity did not correlate with clinical outcomes, suggesting that the disruption of neovessels may not be a mechanism of action of high-volume injection used to treat midsubstance Achilles tendinopathy.…”
Section: Foot and Anklementioning
confidence: 99%
“…The reported outcomes following HVI for treatment of AT are mixed. Although several studies evaluating the effectiveness of HVI with or without steroids (3 case series and 2 RCTs) have found improvement in pain and/or function ranging from 3-wk to 1-year followup (29)(30)(31)(32)(33), other studies have found no superiority of HVI over placebo or correlation of clinical outcomes with change in Doppler flow (34,35).…”
Section: High-volume Injectatementioning
confidence: 99%
“…The presence of neovascularisation has been well established in various tendinopathies 14. Although several studies in recent years have identified that while this ingrowth of blood vessels may be common, its precise function remains unclear; and while hypotheses suggest these may be related to tendon hypoxia,48 their presence poorly correlates with symptoms49–51 and neovessels are not necessarily changed by treatments 52 53. In addition to these neovessels, tendinopathy samples have been shown to have higher levels of several neurochemicals directly associated with pain including glutamate, substance P and lactate 54–56.…”
Section: Introductionmentioning
confidence: 99%
“… 14 Although several studies in recent years have identified that while this ingrowth of blood vessels may be common, its precise function remains unclear; and while hypotheses suggest these may be related to tendon hypoxia, 48 their presence poorly correlates with symptoms 49–51 and neovessels are not necessarily changed by treatments. 52 53 In addition to these neovessels, tendinopathy samples have been shown to have higher levels of several neurochemicals directly associated with pain including glutamate, substance P and lactate. 54–56 The significance of these neurotransmitters remains unclear, but in addition to promoting angiogenesis, these may be triggering a ‘neuropathic-type’ pain by stimulation of the local nerve endings, as it is thought that the development of neovascularity may also be associated with the ingrowth of abnormal sensory nerve endings into tendinopathic tendons.…”
Section: Introductionmentioning
confidence: 99%